The beginnings of public health administration 1867-1876 (Academic Journal of Internal Affairs, 2021)
Looking back to Maria Theresa`s basic health decree, elements of health administration can be defined as part of safety. Specialist authors and lawyers discussing about home affairs administration definitely classify health guidance under the head of home affairs administration. From among the responsible ministries established after the Compromise, health administration got under the control of the ministry of home affairs. The ministry underwent many changes in organisation and competence, but health management remained in the frames of the ministry for the entire time throughout the Compromise, i.e., the duration of the Austro-Hungarian Monarchy. There were intense debates about costeffectiveness, manpower and different competencies of the ministry, as well as the ministers` personal suitability, but it did not influence establishing and operating of professional administrative apparatus. The diversified system of health care duties was handled by a department in the ministry of home affairs. There was an intense debate about the centralized and governmental guidance of public health care, notably to give local governments a bigger power in managing and supervising. However, in this debate centralised managing version proved to be the winner.
Keywords: compromise; health; public health; Ministry of Interior